1999
DOI: 10.1021/jp990062f
|View full text |Cite
|
Sign up to set email alerts
|

Study of Spectral Characteristics, Kinetics, and Equilibria of Radicals Derived from Hydroxy Benzophenones

Abstract: Studies on radical equilibria and the spectral evaluation have been carried out for three monohydroxy-substituted benzophenones (HOBP's) in aqueous solution. The transient ketyl or anion radicals were generated via hydrated electron (eaq -) reaction or dimethyl ketyl radical reaction in a pulse radiolysis experiment. The reactivity of both the undissociated (HOBP) as well as dissociated (-OBP) forms toward these reducing agents were studied. eaq - was found to react with the HOBP's and -OBP's with diffusion-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Singlet states of benzophenone itself and the p-hBP derivative have been found to be very short-lived and undergo ISC to the triplet manifold within a few picoseconds. 7,8 This fast process and the generally high yield for ISC as reported the deactivation channel and the major relaxation pathway of photoexcited benzophenone and p-hBP derivative molecules to the ground state occurs via their T 1 states in the solution phase. The para-HA molecule has a structure similar to the p-hBP molecule where a methyl group in HA is replaced by the second phenyl ring to make p-hBP.…”
Section: Time-resolved Resonance Raman Spectra Of P-hbp In H 2 O/mecnmentioning
confidence: 89%
“…Singlet states of benzophenone itself and the p-hBP derivative have been found to be very short-lived and undergo ISC to the triplet manifold within a few picoseconds. 7,8 This fast process and the generally high yield for ISC as reported the deactivation channel and the major relaxation pathway of photoexcited benzophenone and p-hBP derivative molecules to the ground state occurs via their T 1 states in the solution phase. The para-HA molecule has a structure similar to the p-hBP molecule where a methyl group in HA is replaced by the second phenyl ring to make p-hBP.…”
Section: Time-resolved Resonance Raman Spectra Of P-hbp In H 2 O/mecnmentioning
confidence: 89%
“…Ketyl radicals in solution are known to be more strongly acidic species than the corresponding alcohols. Further, a substantial difference in p K a (in water) values has been found for alkyl and aryl ketyls; for example, for m -hydroxy benzophenone ketyl and dimethyl ketyl, Me 2 C( • )OH, p K a s of 6.5 and 12, respectively, have been reported . The variation of almost 6 p K a units can be associated with the better delocalization of the oxygen's lone pair due to the aromatic system.…”
Section: Discussionmentioning
confidence: 99%
“…12,[20][21][22][23][24][25][26][27][28][29][30][31] For instance, it was found that, depending on the kinds of compounds, introducing the solute-solvent H-bonding can enhance or inhibit the rate of ISC (to triplet) and/or IC (to ground state) to deactivate the initial photopopulated singlet exited state. 20,29,30 There have been many studies that have reported different triplet chemical reactivity in water containing solvent systems as compared to organic solvent systems, and these differences have been mostly associated with the triplet H-bond interaction with solvent water molecule(s), although no explicit solid evidence has been presented. 12,21,27,28,31 The profound H-bonding effects have been mostly attributed to the shifts (sometimes inverse) of electronic levels due to the destabilization of the nπ* states and stabilization of the ππ* states.…”
Section: Introductionmentioning
confidence: 99%